Firefighters' Physical Activity: Relation to Fitness and Cardiovascular Disease Risk - Durand, Gerardo; Tsismenakis, Antonios J.; Jahnke, Sara A.; Baur, Dorothee M.; Kales, Stefanos N.; Christophi, Costas A. (My University, 2011)
DURAND, G., A. J. TSISMENAKIS, S. A. JAHNKE, D. M. BAUR, C. A. CHRISTOPHI, and S. N. KALES. Firefighters' Physical Activity: Relation to Fitness and Cardiovascular Disease Risk. Med. Sci. Sports Exerc., Vol. 43, No. 9, pp. 1752-1759, 2011. Purpose: Cardiovascular disease (CVD) accounts for 44% of on-duty deaths among US firefighters with a markedly higher event risk during strenuous duties compared with nonemergencies. Sedentary persons are most susceptible to such CVD event-triggering due to irregular bouts of vigorous physical activity (PA). Conversely, regular PA and increased levels of cardiorespiratory fitness (CRF) protect against CVD triggering. Therefore, the present study evaluates PA measures in structural firefighters and their relationship to CRF and CVD risk factors. Methods: Cross-sectional cohort study of 527 Midwestern career firefighters. PA frequency, duration, and intensity measures from a questionnaire along with total weekly aerobic exercise were analyzed. CRF was measured by maximal exercise tolerance testing. CVD risk parameters included body composition, blood pressure, and metabolic profiles. Group differences were compared using general linear models. Results: Measures of increasing frequency, duration, intensity of PA, and total weekly exercise (min) were significantly associated with higher CRF (P < 0.001) after adjustment for age, body mass index (BMI), and smoking status. After multivariate adjustment, increasing PA frequency was significantly associated with reduced total cholesterol-HDL ratio, triglycerides, and glucose, as well as HDL increments. Increasing BMI category was associated with significant decrements in CRF and unfavorable dose-response trends in CVD risk factors (P < 0.001), even for those reporting very frequent, sustained, and intense PA. Conclusions: Increasing PA has beneficial independent effects on CRF, and PA frequency has similar favorable effects on CVD risk profiles. Whereas PA was beneficial regardless of BMI category, increasing BMI category had strong independent unfavorable effects. PA should be strongly encouraged for all firefighters with the highest priority given to PA frequency, followed by PA duration and intensity.
Keywords: Exercise; Mets; Occupational; Epidemiology; Metabolic